Vocabulary, Metalinguistic Awareness and Language Dominance Among Bilingual Preschool Children - Altman, Carmit; Goldstein, Tamara; Armon-Lotem, Sharon (Frontiers in Psychology, 2018)
Awareness of language structure has been studied in bilinguals, but there is ‎limited research on how language dominance is related to metalinguistic awareness, ‎and whether metalinguistic awareness predicts vocabulary size. The present study aims ‎to explore the role of language dominance in the relation between vocabulary size in ‎both languages of bilingual children and metalinguistic awareness in the societal ‎language. It evaluates the impact of two metalinguistic awareness abilities, ‎morphological and lexical awareness, on receptive and expressive vocabulary size. This ‎is of a special interest since most studies focus on the impact of exposure on ‎vocabulary size but very few explore the impact of the interaction between ‎metalinguistic awareness and dominance. 5-6-year-old preschool children with typical ‎language development participated in the study: 15 Russian-Hebrew bilingual children ‎dominant in the societal language (SL) Hebrew, 21 Russian-Hebrew bilingual children ‎dominant in the heritage language (HL-Russian) and 32 monolingual children. ‎Dominance was determined by relative proficiency, based on standardized tests in the ‎two languages. Tasks of morphological and lexical awareness were administered in ‎SL-Hebrew, along with measures of receptive and expressive vocabulary size in both ‎languages. Vocabulary size in SL-Hebrew was significantly higher for SL-dominant ‎bilinguals (who performed like monolinguals) than for HL-dominant bilinguals while ‎HL-Russian vocabulary size was higher for HL-dominant bilinguals than for SL-‎dominant bilinguals. A hierarchical regression analyzing the relationship between ‎vocabulary size and metalinguistic awareness showed that dominance, lexical ‎metalinguistic awareness and the interaction between the two were predictors of both ‎receptive and expressive vocabulary size. Morphological metalinguistic awareness was ‎not a predictor of vocabulary size. The relation between lexical awareness and SL-‎vocabulary size was limited to the HL-dominant group. HL-dominant bilinguals relied ‎on lexical metalinguistic awareness, measured by fast mapping abilities, that is, the ‎abilities to acquire new words, in expanding their vocabulary size, whereas SL-‎dominant bilinguals and monolinguals did not. This difference reflects the milestones ‎of lexical acquisition the different groups have reached. These findings show that ‎metalinguistic awareness should also be taken into consideration when evaluating the ‎variables that influence vocabulary size among bilinguals though in different ways in ‎different dominance groups. ‎